Community Organizing the Development of Inclusive as Sustainable Livelihoods in the Era of Pandemic COVID-19 (Descriptive Study of Rural Tambakmekar district. Subang, West Java) - Farah Tri Apriliani; Rd. Ahmad Buchari; Kurnia Muhamad Ramdhan; Nita Astuti Suryana; Muhammad Fahrezi; Ashrina Qurrotu A’yunina (Aliansi, 2022)
Pandemic Covid-19 that occurred in Indonesia have a considerable impact on the several sectors, one of which isin the tourism sector. As a result, around 98.2% tourist villages were temporarily suspended during the Covid-19 pandemic. Meanwhile, the tourism sector is inclusive and able to involve as many people as possible in development. The participation of local communities can have an impact on improving the economy, which in turn has an impact on reducing the poverty level of the community as well as opening up new jobs that can reduce poverty. In this paper, tourism development will be focused on the development of the Tambakmekar Tourism Village located in Subang Regency, West Java. So, this study aims to find out how Tambakmekar Village can become a sustainable livelihood for the surrounding community during the Covid-19 pandemic. The research method used is descriptive qualitative by using the research subject of the Tambakmekar Village community and using primary and secondary data. The results of the research are poured into the community organizing stage which includes 1) integration, 2) mapping of issues, problems, and community potentials, 3) designing joint actions, 4) implementing tourism village development activities, and 5) monitoring and evaluation. There are findings that community participation in village inclusive development is active because of the focus of tourism management in each RW (Rukun Warga) area, thus supporting the utilization of village potential in sustainable livelihoods.